Quality Management in the Development of Teacher Professionalism at State Senior High School 17 Bone - Nasruddin Nasruddin; Djuwairiah Ahmad; Alwan Subhan; Muhammad Ramli; Mardiah Hasan (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the application of quality management in the development of teacher professionalism at SMA Negeri 17 Bone through a qualitative, descriptive-interpretive approach. The focus of the study is directed at the stages of planning, implementation, and the impact of quality management on teachers' pedagogic, professional, social, and personality competencies. Data were collected through observation, in-depth interviews, and documentation studies, then analyzed descriptive-inductively. The results of the study show that quality management planning has been systematically prepared through needs analysis, selective recruitment, and the preparation of teacher capacity development programs involving various stakeholders. The implementation of quality management is realized through continuous training, academic supervision, and professional coaching, although the effectiveness of supervision still tends to be administrative. The implementation of quality management has a positive impact on improving teacher competence, especially in pedagogic, professional, and work ethic aspects, but strengthening the culture of quality and learning innovation still requires continuous reflective mentoring. This research emphasizes the importance of consistency of instructional leadership and a supervisory system oriented towards continuous improvement in supporting teacher professionalism.